Support for Visual Languages Evolution in DSM-platform QReal - T. Y. Agapova; T. A. Bryksin (Моделирование и анализ информационных систем, 2014)
Like other software artefacts, DSMLs evolve in time. When a DSML changes, instance models might no longer conform to the new DSML metamodel and hence cannot be manipulated with a modelling tool. Therefore, a need for models migration to a new version of metamodel arises. Today, various approaches to this problem exist - from entirely manual to mostly automated. This paper describes a hybrid approach to model migration implemented in DSM platform QReal, which is being developed by the research group of Software Engineering Chair of St. Petersburg State University. That DSM platform implies some specific requirements, such as the support of metamodel interpretation and metamodeling “on the fly” modes. The presented approach realizes model migration when using one of those specific features.